Recent Applications of the (TMS)3SiH Radical-Based Reagent - Chryssostomos Chatgilialoglu; Jacques Lalevée (Molecules, 2012)
This review article focuses on the recent applications of tris(trimethylsilyl)silane as a radical-based reagent in organic chemistry. Numerous examples of the successful use of (TMS)3SiH in radical reductions, hydrosilylation and consecutive radical reactions are given. The use of (TMS)3SiH allows reactions to be carried out under mild conditions with excellent yields of products and remarkable chemo-, regio-, and stereoselectivity. The strategic role of (TMS)3SiH in polymerization is underlined with emphasis on the photo-induced radical polymerization of olefins and photo-promoted cationic polymerization of epoxides.